(Implementasi Pendidikan dalam Menumbuhkan Jiwa Kewirausahaan di Perguruan Tinggi ) Studi pada Perguruan Tinggi Muhammadiyah dan Non- Muhammadiyah - Sofia Wijayanti Rahaded (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2023)
The role of educational institutions in preparing learning strategies, training and facilitation in the field of entrepreneurship is not only for students in management science or business economics but also across disciplines. This strategy is needed to be able to create new jobs so as to reduce unemployment and other social inequalities. This research method is a library research using articles, journals and data from the Central Statistics Agency for 2022. The research data is presented descriptively using an analysis of entrepreneurial characteristics. The result is that the institution is ready to prepare students to graduates to have an entrepreneurial spirit and have been facilitated and the student's willingness to become an entrepreneur already exists, but a brave mentality is needed for entrepreneurship. The most important entrepreneurial principle is to be brave or out of fear of failure.